1995
DOI: 10.1096/fasebj.9.13.7557026
|View full text |Cite
|
Sign up to set email alerts
|

The gerontogenes age‐1 and daf‐2 determine metabolic rate potential in aging Caenorhabditis elegans

Abstract: Mutations in the genes age-1 and daf-2 extend life span of Caenorhabditis elegans by 100 and 200%, respectively, in axenic culture. Adult worms that are mutant in either of these genes have higher metabolic capacities, called metabolic rate potentials, at all ages and the extension of their life expectancies are positively correlated with the increases of metabolic rate potential. The activities of catalase, superoxide dismutase, isocitrate dehydrogenase, isocitrate lyase, and malate synthase are all higher re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
2
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(83 citation statements)
references
References 6 publications
7
73
2
1
Order By: Relevance
“…Extension of lifespan by DR was found to occur in chico 1 flies (Clancy et al, 2002). This finding is consistent with similar studies performed in C. elegans (Vanfleteren & De Vreese, 1995;Lakowski & Hekimi, 1998) and, potentially, mice (Bartke, 2001). Yet when chico 1 mutant lifespan was examined over a range of nutritional conditions, it was found to peak at a higher level of nutrition than that of wildtype flies (Clancy et al, 2002) (Fig.…”
Section: Six Ways To Avoid Being Misled By Lifespan Interaction Studiessupporting
confidence: 90%
See 1 more Smart Citation
“…Extension of lifespan by DR was found to occur in chico 1 flies (Clancy et al, 2002). This finding is consistent with similar studies performed in C. elegans (Vanfleteren & De Vreese, 1995;Lakowski & Hekimi, 1998) and, potentially, mice (Bartke, 2001). Yet when chico 1 mutant lifespan was examined over a range of nutritional conditions, it was found to peak at a higher level of nutrition than that of wildtype flies (Clancy et al, 2002) (Fig.…”
Section: Six Ways To Avoid Being Misled By Lifespan Interaction Studiessupporting
confidence: 90%
“…Given that daf-2(e1370) is a class 2 allele, interaction studies with clk-1 , eat-2 , dietary restriction, maleness or germline ablation may potentially be confused by the presence of some of the many pleiotropic defects. For example, the reduction of feeding by daf-2(e1370) adults at higher temperatures may confound studies of interactions between daf-2 and dietary restriction (Vanfleteren & De Vreese, 1995;Lakowski & Hekimi, 1998), or metabolic rate (Van Voorhies & Ward, 1999;Vanfleteren & De Vreese, 1995). Moreover, studies of interactions between daf-12 (which mediates TGF-β signalling) and different alleles of daf-2 have demonstrated that the results of interaction studies may depend upon whether a class 1 or a class 2 daf-2 allele is present (Larsen et al ., 1995;Gems et al, 1998).…”
Section: Effects On Survival Through More Than One Mechanismmentioning
confidence: 99%
“…The dauer stage represents the natural ability of C. elegans to survive for an extended period during adverse conditions. Mutations in certain genes that regulate dauer formation are known to result in changes of the adult life span (Finch and Ruvkun, 2001;Jia et al, 2004;Vanfleteren and De Vreese, 1995), including genes for insulin/IGF-1 signaling (Gems et al, 1998;Kenyon et al, 1993). We aimed to identify changes in transcript abundance common to both types of extended longevity, which may represent a shared mechanism for modulating life span.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the RNAi screens show that a knockdown in expression of the nucleus-encoded subunits of cytochrome c oxidase (F26E4.6, F26E4.9 Y37D8A.1 and W09C5.8) extends longevity, albeit with reduced growth and fecundity. Although a link between mutants with lowered metabolic rate and longevity has been established in C. elegans (Vanfleteren and De Vreese, 1995), it remains a possibility that the nematode may extend longevity not only by reducing oxidative phosphorylation, but by making it more efficient and reducing its production of ROS. A higher ratio of complex IV to complex III activity might accomplish this.…”
Section: Discussionmentioning
confidence: 99%
“…The daf-16 gene encodes for a forkhead transcription factor, which regulates the activity of numerous genes. The specific genes are currently unknown, but daf-2 mutants have increased levels of catalase, superoxide dismutase, isocitrate dehydrogenase, isocitrate lyase, malate synthase and lower levels of acid phosphatase and alkaline phosphatase (98), demonstrating that a large number of enzymatic proteins are likely affected.…”
Section: Insulin Resistance and Longevity: Beyond Glucosementioning
confidence: 99%